THE FORTRESSES IN RN MACEDONIJA IN FUNCTION FOR ENRICHING TO TOURIST OFFER - Dimitrov, Nikola V (Journal of process management and new technologies, 2021)
The tourist potentials of the medieval fortresses in RN Macedonia as a medieval heritage in the context of cultural and historical tourism are often neglected, but the practice in other European and even in Balkan countries shows that this segment of history can be used at a very high level.The purpose of this paper is to explore the fortresses in order to enrich the tourist offer in RN. Macedonia.            Archaeological excavations have identified about eighty medieval fortresses and other fortifications on the territory of the country.The mentioned fortified settlements appear in different time periods from prehistory, through antiquity to the Middle Ages.There is a generally accepted opinion that the formation of tourist cultural routes would lead to better protection and presentation of the cultural monument and their activation in use for tourist purposes.The formation of a new tourist product is a big step in the formation of an attractive tourist offer, and in this case it is the Macedonian medieval fortresses.In the framework of this paper, the research is aimed at a narrow selection of medieval fortresses that can offer attractive content to tourists.The analysis and evaluation uses known and recognized qualitative - quantitative and comparative research methods, procedures, criteria and activities for tourism valorization.
Keywords: fortress; tourism; historical monuments; valorization; RN Macedonia